Ternary positive electrode material for lithium-ion batteries and its manufacturing method

By forming a wrinkled outer coating on the high-nickel oxide positive electrode material, the problem of capacity attenuation and insufficient cycle life is solved, and the energy density and cycle performance are improved.

JP2025507806AActive Publication Date: 2025-03-21HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024551597
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-03-21
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

The high-nickel layer oxide positive electrode material has capacity attenuation problems during the circulation process, resulting in insufficient energy density and cycle life of lithium-ion batteries, and the existing water washing and surface coating methods have problems such as production complexity and reduced energy density.

Method used

A ternary positive electrode material with a wrinkled outer coating is adopted, and the core material is a lithium composite metal oxide of nickel, cobalt and manganese. The outer coating is composed of lithium metal oxide with high cobalt content. The wrinkled coating is formed through a multi-stage high-temperature sintering process.

Benefits of technology

It effectively reduces the residual lithium compounds on the surface, improves the characteristic capacity and cycle life of the material, and reduces the conductivity growth and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507806000001_ABST
    Figure 2025507806000001_ABST
Patent Text Reader

Abstract

The present invention discloses a ternary positive electrode material for lithium-ion batteries. The ternary positive electrode material has a coated structure, the core includes a lithium composite metal oxide, the outer coating layer is wrinkled, the wrinkled outer coating layer coats the surface of the lithium composite metal oxide, and the outer coating layer is mainly a cobalt-containing lithium metal oxide. The method for producing the positive electrode material includes mixing a lithium source and a ternary precursor material in a molar ratio, carrying out multi-stage high-temperature sintering under an oxygen atmosphere, and cooling to room temperature to obtain a lithium composite metal oxide, which is mixed with a cobalt source or a compound of a cobalt source and an M element, and then sintering under an oxygen atmosphere to obtain a ternary positive electrode material. The product of the present invention can significantly reduce the surface residual lithium compounds of high nickel materials, effectively improve the specific capacity and cycle life of the materials, and at the same time, significantly reduce the DCR of the materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium battery positive electrode material and a method for producing the same, and more particularly to a lithium battery ternary positive electrode material and a method for producing the same. [Background technology]

[0002] Rechargeable lithium-ion batteries have been widely applied in electronic devices, household appliances, and power tools in recent years due to their advantages of high energy density, high operating voltage, low self-discharge rate, long cycle life, and environmental friendliness. The great success of lithium-ion batteries in portable electronic products has also promoted the development and application of pure electric vehicles.

[0003] With the rapid development of electric vehicles and large-scale energy storage fields, the energy density and cycle life of rechargeable lithium-ion batteries at the current stage are facing great challenges. High-nickel layered oxide cathode materials are considered to be the most promising candidate materials due to their high energy density and relatively low manufacturing costs. However, with the increase in nickel content, high-nickel layered oxides have serious capacity fade problems during cycling. The unstable lithium residues (Li2CO3 and LiOH) on the surface of the material cause capacity fade, while the similar ionic radii of lithium ions and divalent nickel ions form lithium-nickel mixed discharges, which cause the layered cathode material to transition to a rock salt phase as cycling progresses, resulting in a significant increase in the DCR of the material and ultimately causing serious capacity fade. This structural instability is also manifested in the occurrence of intercrystalline cracks in high-nickel layered cathode materials during cycling, which causes the electrolyte to erode the layered material along the cracks, resulting in a shorter cycle life of high-nickel layered materials.

[0004] The most direct method in the current industry is to carry out a water washing process on high-nickel materials to achieve the purpose of reducing residual lithium compounds. However, the water washing process first increases the complexity of the production process and destroys the surface structure of the material to a certain extent, so that the cycle life and energy density of the material cannot meet the application requirements. Another effective way to overcome the decomposition of high-nickel positive electrode materials is to carry out a surface coating coating, which can protect the positive electrode material from the erosion of the electrolyte, and is an intuitive and effective method. However, most inactive coating materials only stick or attach to the positive electrode material, and are easily mechanically peeled off by external forces. At the same time, these inactive coating materials also reduce the active material specific gravity of the positive electrode material, which further reduces the energy density. Therefore, there is a need to develop a surface-coated high-nickel layered oxide positive electrode material that not only has activity, but also reduces the surface residual lithium, improves the capacity characteristics and cycle characteristics, and reduces the growth of the material DCR. Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a ternary positive electrode material for lithium ion batteries, which can significantly reduce the surface residual lithium compounds of high nickel materials, effectively improve the specific capacity and cycle life of the materials, and at the same time significantly reduce the DCR of the materials, in order to overcome the shortages and defects described in the background art. Meanwhile, another aspect of the present invention further provides a method for preparing the ternary positive electrode material for lithium ion batteries. [Means for solving the problem]

[0006] To solve the above problems, the technical solution proposed by the present invention is a ternary cathode material for a lithium-ion battery, wherein the ternary cathode material has a coated structure, the core of the coated structure contains a lithium composite metal oxide, the lithium composite metal oxide contains nickel, cobalt, and manganese, the outer coating layer of the coated structure has a wrinkled shape, and the wrinkled outer coating layer covers the surface of the lithium composite metal oxide, and the wrinkled outer coating layer is mainly a cobalt-containing lithium metal oxide.

[0007] In the above-described ternary cathode material for a lithium-ion battery, preferably, the lithium composite metal oxide in the ternary cathode material is Li a Ni x Co y Mn 1-x-y It may be represented by O2, and 1.0 ≦ a ≦ 1.15, 0.8 ≦ x < 1, 0 < y ≦ 0.2, 0 < 1 - x - y. Further, the outer coating layer of the ternary cathode material is a cobalt-containing lithium metal oxide, the coating layer contains a plurality of species among Li, Co, O, and M elements, and the outer coating layer is Li m CoM n It may be represented by O2, where M is one or more selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y, and 0.5 ≦ m < 1, 0 ≦ n ≦ 0.2. The ternary cathode material is Li a Ni x Co y Mn 1-x-y O2·Li m CoM n It is represented by O2, and 1.0 ≦ a ≦ 1.15, 0.8 ≦ x < 1, 0 < y ≦ 0.2, 0 < 1 - x - y, where M is one or more selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y as a doping element. The content of Ni in the ternary cathode material is preferably 80 mol% or more based on the content of all transition metals.

[0008] In the above-mentioned ternary positive electrode material for lithium ion batteries, the particle size of the ternary positive electrode material is preferably in the range of 1.0 to 10.0 μm, more preferably in the range of 1.0 to 5.0 μm. By optimizing the particle size, the objective of maximizing the capacity characteristics can be achieved.

[0009] In the above-mentioned ternary positive electrode material for a lithium ion battery, preferably, the specific surface area of ​​the ternary positive electrode material is 0.3 to 0.9 m 2 / g, and more preferably, the specific surface area is 0.7 to 0.9 m 2 / g. After being wrinkled, the specific surface area of ​​the ternary positive electrode material is increased, and the particle size and specific surface area of ​​the material are comprehensively adjusted to achieve a comprehensive improvement in the overall performance.

[0010] In the above-mentioned ternary positive electrode material for a lithium ion battery, preferably, the outer coating layer further contains an M element, and M as a doping element is one or more elements selected from the group consisting of Co, Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y.

[0011] In the above-mentioned ternary positive electrode material for a lithium ion battery, the coating thickness of the outer coating layer is preferably 0.1 to 0.6 μm, and more preferably 0.1 to 0.4 μm.

[0012] In the above-mentioned ternary positive electrode material for lithium ion batteries, preferably, the cobalt-containing lithium metal oxide in the outer coating layer is obtained by reacting a cobalt source with the lithium compounds (such as Li2CO3 and LiOH) remaining on the surface layer of the lithium composite metal oxide. In this way, the purpose of reducing the residual lithium compounds on the material surface can be achieved, and the residual lithium can be effectively reduced by adjusting the content of cobalt in the wrinkled coating layer to form an electrochemically active cobalt-containing lithium metal oxide. In addition, the electrochemically active wrinkled coating layer has a larger specific surface area than the normal coating layer, so that it can accelerate the conduction of lithium ions and electrons, further improve the rate performance of the material, and reduce the DCR growth.

[0013] In the above-mentioned ternary positive electrode material for lithium ion batteries, the content of cobalt in the outer coating layer is preferably 6000 to 32000 ppm, more preferably 6000 to 19000 ppm. On the other hand, if an excessive amount of cobalt source is added, the excess cobalt source is converted to inactive Co3O4 at high temperatures, and the inactive Co3O4 inhibits the conduction of lithium ions and electrons, thereby reducing the overall performance of the material.

[0014] In the above-mentioned ternary positive electrode material for a lithium ion battery, preferably, I in the XRD pattern of the ternary positive electrode material (003) / I (104) The ratio is 1.5 to 3.0. (003) / I (104) The higher the ratio, the better the layered structure of the material and the better its electrochemical performance.

[0015] In the above-mentioned ternary positive electrode material for lithium ion batteries, preferably, the wrinkle degree X of the ternary positive electrode material under a scanning electron microscope is in the range of 0.1 to 0.8, where X=h / t, where h is the height of a single wrinkled morphology on the crystal grain surface of the single ternary positive electrode material, 20 nm≦h≦120 nm, and t is the width of a single wrinkled morphology on the crystal grain surface of the single ternary positive electrode material, 100 nm≦t≦200 nm. Since there are N wrinkles on the crystal grain surface of the ternary positive electrode material, X is within a certain range, and generally is preferably 0.1 to 0.8.

[0016] As a general technical idea, the present invention further provides a method for preparing a ternary positive electrode material for a lithium-ion battery, the method comprising: A lithium source and a ternary precursor material (e.g., Ni x Co y Mn 1-x-y OH) in a molar ratio of 1 to 1.15:1, and after mixing, performing multi-stage high-temperature sintering (preferably two stages) in an oxygen atmosphere, and cooling to room temperature to obtain a lithium composite metal oxide; and step 2) of mixing the lithium composite metal oxide obtained in step 1) with a cobalt source or a compound of a cobalt source and an M element, and then sintering the mixture in an oxygen atmosphere to obtain a ternary positive electrode material, The amount of the cobalt source added is 10,000 ppm to 50,000 ppm (based on the lithium composite metal oxide produced in step 1).

[0017] In the above-mentioned manufacturing method, the cobalt source is selected from cobalt hydroxide or cobalt oxyhydroxide. The acidic cobalt source may destroy the surface structure of high nickel materials, leading to a decrease in electrochemical performance.

[0018] In the above-mentioned manufacturing method, preferably, the high-temperature sintering in step 1) is a two-stage calcination, the temperature range of the first stage calcination is 400-600°C, the sintering time is 2-4 hours, and the temperature range of the second stage calcination is 600-1000°C, the sintering time is 8-15 hours.

[0019] In the above-mentioned manufacturing method, the sintering temperature in step 2) is preferably 600 to 900° C. and the sintering time is 5 to 12 hours, and preferably 650 to 850° C. and the sintering time is 6 to 9 hours.

[0020] By controlling the sintering temperature and time, the coating effect can be optimized and the optimal wrinkled coating morphology can be achieved. By controlling the sintering temperature and time in step 2), the coating effect can be optimized and the optimal wrinkled coating morphology can be achieved. If the sintering temperature is too low or the time is too short, the cobalt source cannot react with the residual lithium compound components on the material surface, and a uniform coating cannot be formed, resulting in uneven spot-like coating. On the other hand, if the sintering temperature is too high or the time is too long, the molten lithium metal compound on the material surface tends to flatten at high temperatures, and the ideal wrinkled coating cannot be formed.

[0021] In the above-mentioned production method, the lithium source is preferably one or more selected from lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate.

[0022] In the above-mentioned production method, the compound of the M element is preferably a compound of at least one element selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y.

[0023] Based on the cobalt content in the outer coating layer of the product, the amount of the cobalt source added is preferably in the range of 10,000 to 30,000 ppm. Furthermore, the median diameter D50 of the cobalt source in step 2) is 0.8 to 4.0 μm, preferably 1.0 to 2.0 μm. By controlling the median diameter of the cobalt source, the wrinkled coating can be made more uniform, and a high-nickel positive electrode material with better electrochemical performance can be obtained. Effect of the Invention

[0024] Compared with the prior art, the present invention forms a high-nickel (nickel content is 80 mol% or more) NCM positive electrode material by carrying out a wrinkled cobalt coating on a lithium composite metal oxide, and the wrinkled coating layer can effectively remove the lithium residues (lithium hydroxide and lithium carbonate) on the surface of the high-nickel positive electrode material, and form a cobalt-containing lithium metal oxide with electrochemical activity on the surface. The wrinkled coating layer does not destroy the surface structure of the high-nickel material, and can avoid the direct contact between the high-nickel positive electrode material and the electrolyte, thereby increasing the stability of the surface structure and the cycle performance of the material. In addition, the wrinkled coating can construct a coating layer with a stable interface / structure, and the wrinkled coating with a special morphology can increase the specific surface area of ​​the particle material and reduce the residual lithium, thereby improving the ionic and electronic conductivity of the material, further improving the rate performance of the material, and reducing the DCR. In addition, the cobalt-containing lithium metal oxide in the wrinkled coating layer has a certain electrochemical activity, which further improves the capacity properties of the material.

[0025] In order to more clearly describe the technical solutions in the embodiments of the present invention or the prior art, the drawings necessary for the description of the embodiments or the prior art are briefly introduced below. The drawings in the following description are some embodiments of the present invention, and it is obvious that those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Brief description of the drawings]

[0026] [Figure 1] 1 is a scanning electron microscope photograph of the wrinkled-coated high-nickel ternary positive electrode material produced in Example 1 of the present invention. [Diagram 2] FIG. 2 is a particle size distribution diagram based on the legend of a scanning electron microscope photograph of Example 1 of the present invention. [Diagram 3] FIG. 2 is a particle size distribution diagram of the wrinkled-coated high-nickel ternary positive electrode material produced in Example 1 of the present invention. [Figure 4] 1 is an EDS image of a wrinkled coating layer on the surface of the high-nickel ternary positive electrode material prepared in Example 1 of the present invention. [Diagram 5] 1 is an electron microscope probe examination (EMPA) image of the wrinkled-coated high-nickel ternary positive electrode material prepared in Example 1 of the present invention. [Figure 6] 1 is a scanning electron microscope photograph of a cross section of a wrinkled-coated single high-nickel ternary positive electrode material produced in Example 1 of the present invention. [Figure 7] 1 is an XRD pattern of the wrinkled-coated high-nickel ternary positive electrode material prepared in Example 1 of the present invention. [Figure 8] 1 is a scanning electron microscope photograph of the uncoated high-nickel ternary positive electrode material produced in Comparative Example 1. [Figure 9] 1 is a scanning electron microscope photograph of a smooth-coated high-nickel ternary positive electrode material produced in Comparative Example 2. [Figure 10] 1 is a scanning electron microscope photograph of the dot-like coated high-nickel ternary positive electrode material produced in Comparative Example 3. [Figure 11] 1 is a scanning electron microscope photograph of the high-nickel ternary positive electrode material produced in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] In order to facilitate understanding of the present invention, the present invention will be described more comprehensively and in detail below with reference to the drawings and preferred embodiments in the specification, but the scope of protection of the present invention is not limited to the following specific examples.

[0028] All technical terms used below have the same meaning as commonly understood by those skilled in the art unless otherwise defined. The technical terms used in this specification are for describing specific embodiments and do not limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments, equipment, and the like used in the present invention are commercially available or can be produced by existing methods. Example 1

[0030] The method for producing high nickel ternary positive electrode material for lithium ion batteries is as follows. (1) Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Lithium composite metal oxide production Lithium hydroxide monohydrate and 100g of Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was mixed in a molar ratio of 1.05:1, and the mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 A lithium composite metal oxide of O2 was obtained. (2) Wrinkled cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Manufacturing of high nickel ternary positive electrode materials 100g of Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 12300ppm of cobalt hydroxide was added to the O2 lithium composite metal oxide and mixed uniformly. The mixture was then calcined at 720℃ in an oxygen atmosphere with a heating rate of 3℃ / min. The calcination time was 7 hours. After cooling to room temperature, the Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 0.82 A CoO2 high nickel ternary positive electrode material was obtained.

[0031] The high nickel ternary positive electrode material prepared in this embodiment was subjected to FE-SEM testing, and the results are shown in Figure 1. As can be seen from Figure 1, the high nickel ternary positive electrode material prepared in this embodiment has an obvious coating structure, in which the core of the coating structure contains lithium composite metal oxide (i.e., the core material prepared in step (1)), and the lithium composite metal oxide is Li 1.05 Ni 0.83 Co 0.12 Mn 0.05The outer coating layer contained O2 and had a coating structure with obvious wrinkles, and the wrinkled outer coating layer coated the surface of the lithium composite metal oxide, and the wrinkled outer coating layer was mainly composed of cobalt-containing lithium metal oxide (i.e., the coating material produced in step (2)).

[0032] The wrinkled coated high-nickel ternary positive electrode material particles produced in this example had a particle size range of 1.5 to 4.5 μm (see FIG. 2), a median size of 5.62 μm (see FIG. 3), and a specific surface area of ​​0.74 m 2 / g and pH was 11.71. The high-nickel ternary positive electrode material had a specific gravity of 3.48 g / cc and a powder conductivity of 0.023 S / cm. The high-nickel ternary positive electrode material after the wrinkled cobalt coating had a significantly reduced surface lithium residue compared to the lithium composite metal oxide material of step (1) (see Table 1 below), and the contents of lithium hydroxide and lithium carbonate on the sample surface after the wrinkled coating were both significantly reduced.

[0033] [Table 1]

[0034] An EDS test was performed on the wrinkled coating layer of the high-nickel ternary positive electrode material produced in this example, and the results are shown in Figure 4. As can be seen from the EDS results, the wrinkled coating layer is a cobalt-containing lithium metal oxide, which is formed by the reaction of the added cobalt source with the lithium compound remaining on the surface layer of the lithium composite metal oxide, and the cobalt content here is greater than the cobalt content of the high-nickel ternary positive electrode material itself, because it is formed by the reaction of the added cobalt source with the lithium compound remaining on the surface layer of the lithium composite metal oxide, and the cobalt content in the wrinkled coating layer here was 7500 ppm.

[0035] The wrinkled coating layer of the wrinkled-coated high-nickel ternary positive electrode material prepared in this example was further subjected to electron microscope probe analysis (EMPA), and the results are shown in Figure 5. As can be seen from the EMPA test results, the wrinkled cobalt coating layer uniformly covers the material surface, and the coating thickness is about 0.3 μm.

[0036] A scanning electron microscope test was performed on the cross section of the wrinkled high-nickel ternary positive electrode material produced in this example, and the results are shown in Figure 6. As can be seen from the results, the wrinkle degree was 0.21 to 0.63. The "wrinkle degree" in this example is a parameter defined here, and the "wrinkle degree" is represented by X, which means the ratio of the height h of a single wrinkled form on the crystal grain surface of a single high-nickel ternary positive electrode material to its width t, and is represented by the formula X = h / t, and since there are multiple different wrinkles, the X value of the product generally varies in a large range.

[0037] The wrinkled high-nickel ternary positive electrode material produced in this example was subjected to an XRD test (see FIG. 7). (003) / I (104) The ratio was 2.26, and generally, the higher the ratio, the better the crystallinity of the material and the more complete the layer structure.

[0038] The wrinkled high-nickel ternary positive electrode material produced was used as the positive electrode and a metallic lithium sheet was used as the negative electrode to prepare a button battery, and a performance evaluation test of the high-nickel ternary positive electrode material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0-4.3V, and current density 0.1C, and the discharge specific capacity was 207 mAh / g and the coulombic efficiency was 87.8%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 90.3%, and the capacity retention rate was 95.1% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0-4.3V, and current density 0.5C, and the DCR at 10% SOC of the material was 27.8Ω, and the DCR growth after 50 cycles was 25%. The results confirmed that the wrinkled-coated high-nickel ternary positive electrode material can effectively improve the capacity, cycle performance and rate performance, and reduce the DCR value. Example 2

[0039] The method for producing high nickel ternary positive electrode material for lithium ion batteries is as follows. (1) Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Lithium composite metal oxide production Lithium hydroxide monohydrate and 100g of Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was mixed in a molar ratio of 1.05:1, and the mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 A lithium composite metal oxide of O2 was obtained. (2) Wrinkled cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 0.83 CoAl 0.2O2 Manufacturing of high nickel ternary positive electrode materials 100g of Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 12300ppm cobalt hydroxide and 1500ppm aluminum hydroxide were added to the O2 lithium composite metal oxide, mixed uniformly, and then calcined at 710℃ in an oxygen atmosphere with a heating rate of 3℃ / min. The calcination time was 7 hours, and after cooling to room temperature, Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 0.83 CoAl 0.2 O2 high nickel ternary positive electrode material was obtained.

[0040] The FE-SEM test was performed on the high-nickel ternary positive electrode material prepared in this embodiment. As a result, it was found that the high-nickel ternary positive electrode material prepared in this embodiment has an obvious coating structure, the core of the coating structure contains lithium composite metal oxide (i.e., the core material prepared in step (1)), and the lithium composite metal oxide is Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 The outer coating layer of the coating structure contained O2 and had obvious wrinkles, which indicated that the wrinkled outer coating layer covered the surface of the lithium composite metal oxide, and the wrinkled outer coating layer was mainly cobalt-containing lithium metal oxide (i.e., the coating material prepared in step (2)).

[0041] The wrinkled coated high-nickel ternary positive electrode material particles produced in this example had a particle size range of 1.3 to 4.5 μm, a median diameter of 5.48 μm, and a specific surface area of ​​0.78 m 2 / g and pH was 11.68. The high-nickel ternary positive electrode material had a specific gravity of 3.50 g / cc and a powder conductivity of 0.022 S / cm. The high-nickel ternary positive electrode material after the wrinkled cobalt coating was significantly reduced relative to the surface lithium residue of the lithium composite metal oxide material in step (1).

[0042] The wrinkled coating layer of the high nickel ternary positive electrode material produced in this embodiment is subjected to EDS test. From the EDS result, it can be seen that the wrinkled coating layer is a lithium metal oxide containing cobalt and aluminum, where the cobalt content is greater than the cobalt content of the high nickel ternary positive electrode material itself, this is because the cobalt source added reacts with the lithium compound remaining on the surface layer of the lithium composite metal oxide to form, where the cobalt content in the wrinkled coating layer is 7480ppm, and the aluminum content is 1350ppm.

[0043] The wrinkled coating layer of the wrinkled high nickel ternary positive electrode material prepared in this example was further subjected to electron microscope probe analysis (EMPA). As can be seen from the EMPA test results, the wrinkled cobalt coating layer uniformly covers the material surface, and the coating thickness is about 0.32 μm.

[0044] The cross section of the wrinkled coated high nickel ternary positive electrode material produced in this embodiment is subjected to scanning electron microscope examination, the test method is the same as above, and the result shows that the wrinkle degree range is 0.25-0.68.

[0045] The wrinkled coated high nickel ternary positive electrode material produced in this example was subjected to an XRD test. (003) / I (104) The ratio was 2.42, and generally, the higher the ratio, the better the crystallinity of the material and the more complete the layer structure.

[0046] The wrinkled high-nickel ternary positive electrode material was used as the positive electrode and a metallic lithium sheet was used as the negative electrode to prepare a button battery, and a performance evaluation test of the high-nickel ternary positive electrode material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0-4.3V, and current density 0.1C, and the discharge specific capacity was 207 mAh / g and the coulombic efficiency was 88.2%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 91.1%, and the capacity retention rate was 96.1% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0-4.3V, and current density 0.5C, and the DCR at 10% SOC of the material was 29.4Ω, and the DCR growth after 50 cycles was 26%. The results confirmed that the wrinkled-coated high-nickel ternary positive electrode material can effectively improve the capacity, cycle performance and rate performance, and reduce the DCR value, and further co-coating with aluminum can further improve the cycle performance of the material. Example 3

[0047] The method for producing high nickel ternary positive electrode material for lithium ion batteries is as follows. (1) Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 O2 Lithium composite metal oxide production Lithium hydroxide monohydrate and 100g of Ni 0.90 Co 0.05 Mn 0.05 (OH)2 was mixed in a molar ratio of 1.05:1, and the mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 A lithium composite metal oxide of O2 was obtained. (2) Wrinkled cobalt-coated Li 1.05 Ni 0.90 Co 0.05 Mn 0.05O2·Li 0.61 CoAl 0.2 O2 Manufacturing of high nickel ternary positive electrode materials 100g of Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 The O2 lithium composite metal oxide was mixed with 18,500 ppm of cobalt oxyhydroxide and 1,500 ppm of aluminum hydroxide, and then mixed uniformly. The mixture was then calcined at 715°C in an oxygen atmosphere with a heating rate of 3°C / min. The calcination time was 7 hours, and the mixture was cooled to room temperature. 1.05 Ni 0.90 Co 0.05 Mn 0.05 O2·Li 0.61 CoAl 0.2 O2 high nickel ternary positive electrode material was obtained.

[0048] The FE-SEM test was performed on the high-nickel ternary positive electrode material prepared in this embodiment. As a result, it was found that the high-nickel ternary positive electrode material prepared in this embodiment has an obvious coating structure, the core of the coating structure contains lithium composite metal oxide (i.e., the core material prepared in step (1)), and the lithium composite metal oxide is Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 The outer coating layer of the coating structure contained O2 and had obvious wrinkles, which indicated that the wrinkled outer coating layer covered the surface of the lithium composite metal oxide, and the wrinkled outer coating layer was mainly cobalt-containing lithium metal oxide (i.e., the coating material prepared in step (2)).

[0049] The wrinkled coated high-nickel ternary positive electrode material particles produced in this example had a particle size range of 1.2 to 4.6 μm, a median diameter of 5.21 μm, and a specific surface area of ​​0.82 m 2 / g and pH was 11.73. The high-nickel ternary positive electrode material had a specific gravity of 3.48 g / cc and a powder conductivity of 0.023 S / cm. The high-nickel ternary positive electrode material after the wrinkled cobalt coating was significantly reduced relative to the surface lithium residue of the lithium composite metal oxide material in step (1).

[0050] The wrinkled coating layer of the high nickel ternary positive electrode material produced in this embodiment is subjected to EDS test. From the EDS result, it can be seen that the wrinkled coating layer is a lithium metal oxide containing cobalt and aluminum, where the cobalt content is greater than the cobalt content of the high nickel ternary positive electrode material itself, this is because the cobalt source added reacts with the lithium compound remaining on the surface layer of the lithium composite metal oxide to form, where the cobalt content in the wrinkled coating layer is 16700ppm, and the aluminum content is 1380ppm.

[0051] The wrinkled coating layer of the wrinkled high nickel ternary positive electrode material prepared in this example was further subjected to electron microscope probe analysis (EMPA). As can be seen from the EMPA test results, the wrinkled cobalt coating layer uniformly covers the material surface, and the coating thickness is about 0.39 μm.

[0052] Scanning electron microscopy examination of the cross-section of the wrinkled coated high nickel ternary cathode material produced in this example showed that the wrinkle degree range was about 0.19 to 0.71.

[0053] The wrinkled coated high nickel ternary positive electrode material produced in this example was subjected to an XRD test. (003) / I (104) The ratio was 2.35, and generally, the higher the ratio, the better the crystallinity of the material and the more complete the layer structure.

[0054] The wrinkled high-nickel ternary positive electrode material produced was used as the positive electrode and a metallic lithium sheet was used as the negative electrode to prepare a button battery, and a performance evaluation test of the high-nickel ternary positive electrode material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0-4.3V, and current density 0.1C, and the discharge specific capacity was 206mAh / g and the coulombic efficiency was 89.1%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 90.6%, and the capacity retention rate was 95.9% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0-4.3V, and current density 0.5C, and the DCR at 10% SOC of the material was 28.2Ω, and the DCR growth after 50 cycles was 25%. The results confirmed that the wrinkled-coated high-nickel ternary positive electrode material can effectively improve the capacity, cycle performance and rate performance, and reduce the DCR value, and further co-coating with aluminum can further improve the cycle performance of the material. Comparative Example 1

[0055] In this comparative example, Li without a coating layer 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material was manufactured. The specific manufacturing method is as follows: Lithium hydroxide monohydrate and 100g of Ni 0.83 Co 0.12 Mn 0.05 The mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and the Li without a coating layer was obtained. 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material was obtained.

[0056] Comparative Example 1 had the same nickel-cobalt-manganese composition as Example 1, but was not coated. The material produced in Comparative Example 1 was subjected to an FE-SEM test, and the results are shown in FIG. 8. The high-nickel ternary positive electrode material produced in Comparative Example 1 did not have a clear coating layer and had a smooth surface. The particle diameter range of the high-nickel ternary positive electrode material particles produced in Comparative Example 1 was 1.0 to 4.8 μm, the median diameter was 5.46 μm, and the specific surface area was 0.73 m. 2 The material had a specific gravity of 3.40 g / cc and a powder conductivity of 0.017 S / cm. The high nickel ternary cathode material produced in Comparative Example 1 was subjected to XRD testing to determine its I (003) / I (104) The ratio was 1.84. Compared with Example 1, the crystallinity of Comparative Example 1 was relatively poor, and the layer structure was not as complete as that of Example 1.

[0057] A button battery was prepared using the uncoated high nickel ternary positive electrode material produced in Comparative Example 1 as the positive electrode and a metallic lithium sheet as the negative electrode, and a performance evaluation test of the material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0 to 4.3V, and current density 0.1C, and the discharge specific capacity was 201 mAh / g and the coulombic efficiency was 87.2%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 86.7%, and the capacity retention rate was 90.3% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0 to 4.3V, and current density 0.5C, and the result showed that the DCR at 10% SOC of the material was 55.6Ω, and the DCR growth after 50 cycles was 87.7%. From the results, it was confirmed that the uncoated high-nickel ternary positive electrode material was clearly inferior to the products produced in the examples of the present invention in terms of capacity, cycle performance, rate performance, and DCR growth. Comparative Example 2

[0058] In this comparative example, the smooth cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05The O2 high nickel ternary positive electrode material was manufactured. The specific manufacturing method is as follows: (1) Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Production of lithium-containing metal oxides Lithium hydroxide monohydrate and 100g of Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was mixed in a molar ratio of 1.05:1, and the mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 lithium-containing metal oxide was obtained. (2) Smooth Cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Manufacturing of high nickel ternary positive electrode materials 100g of Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 12355ppm of cobalt hydroxide was added to the lithium-containing metal oxide, mixed uniformly, and then calcined at 950℃ in an oxygen atmosphere with a heating rate of 3℃ / min. The calcination time was 7 hours. After cooling to room temperature, a smooth cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 high nickel positive electrode material was obtained.

[0059] Comparative Example 2 had the same nickel-cobalt-manganese composition as Example 1, and was simultaneously subjected to a cobalt coating treatment, but a smooth coating layer was produced in this comparative example. An FE-SEM test was performed on the material produced in Comparative Example 2, and the results are shown in FIG. 9. The high-nickel ternary positive electrode material produced in Comparative Example 2 had a clear coating layer, but the coating layer did not have a special form and smoothly coated the surface of the lithium-containing metal oxide material. The particle diameter range of the smooth-coated high-nickel positive electrode material particles produced in Comparative Example 2 was 1.0 to 4.6 μm, the median diameter was 5.16 μm, and the specific surface area was 0.71 m. 2 The material had a specific gravity of 3.43 g / cc and a powder conductivity of 0.018 S / cm. The coating layer of the high nickel ternary cathode material produced in Comparative Example 2 was subjected to EDS testing. As can be seen from the EDS results, the coating layer was a cobalt-containing lithium metal oxide, where the content of cobalt in the coating layer was 7600 ppm. The high nickel ternary cathode material produced in Comparative Example 2 was subjected to XRD testing to determine its I (003) / I (104) The ratio was 2.17.

[0060] The smooth cobalt-coated high-nickel ternary positive electrode material was used as the positive electrode and a metallic lithium sheet was used as the negative electrode to prepare a button battery, and a performance evaluation test of the material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0-4.3V, and current density 0.1C, and the discharge specific capacity was 206mAh / g and the coulombic efficiency was 87.8%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 87.2%, and the capacity retention rate was 91.4% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0-4.3V, and current density 0.5C, and the DCR at 10% SOC of the material was 43.1Ω, and the DCR growth after 50 cycles was 43%. From these results, it was confirmed that the smooth cobalt-coated high-nickel ternary positive electrode material is close to the wrinkled-coated high-nickel ternary positive electrode material in terms of initial capacity, but is inferior to the wrinkled-coated high-nickel ternary positive electrode material of the present invention in terms of rate performance, cycle performance, and DCR growth. Comparative Example 3

[0061] Cobalt-aluminum co-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 1.1 CoAl 0.4 The O2 high nickel positive electrode material is produced, and the production method is as follows: (1) Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2 Production of lithium-containing metal oxides Lithium hydroxide monohydrate and 100g of Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was mixed in a molar ratio of 1.05:1, and the mixed raw materials were heated from room temperature to 500°C at a heating rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850°C and calcined for 12 hours, naturally cooled to room temperature, and Li 1.05 Ni 0.83 Co 0.12 Mn 0.05O2 lithium-containing metal oxide was obtained. (2) Cobalt-aluminum co-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 1.10 CoAl 0.4 O2 Manufacturing of high nickel ternary positive electrode materials 100g of Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 Add 5000 ppm cobalt hydroxide and 1500 ppm aluminum hydroxide to the lithium-containing metal oxide, mix uniformly, and then heat at a rate of 3°C / min in an oxygen atmosphere at 710°C. The calcination time is 7 hours. After cooling to room temperature, the cobalt-coated Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 O2·Li 1.10 CoAl 0.4 O2 high nickel positive electrode material was obtained.

[0062] In Comparative Example 3, the amount of cobalt hydroxide added was small, 5000 ppm, and the morphology of the high-nickel positive electrode material produced with cobalt-aluminum co-coating was a dot-like coating. The nickel-cobalt-manganese composition was the same as that of Example 2, and cobalt and aluminum were simultaneously coated. The material produced in Comparative Example 3 was subjected to an FE-SEM test, and the results are shown in FIG. 10. The high-nickel ternary positive electrode material produced in Comparative Example 3 has a coating layer, but the surface is a large amount of dot-like coating, which is significantly different from the wrinkled coating. This shows that the reduction in the amount of cobalt source added affects the formation of the wrinkled morphology, and when the amount of cobalt source added is small, a uniform wrinkled coating cannot be formed, and a dot-like coating is formed. The particle size range of the high-nickel ternary positive electrode material particles produced in Comparative Example 3 was 1.4 to 4.2 μm, the median diameter was 5.21 μm, and the specific surface area was 0.84 m 2 The material had a specific gravity of 3.46 g / cc and a powder conductivity of 0.020 S / cm. The dotted cobalt-aluminum coated high nickel ternary positive electrode material prepared in Comparative Example 3 was subjected to XRD testing to determine its I (003) / I (104) The ratio was 2.24.

[0063] The dot-like cobalt-aluminum-coated high-nickel ternary positive electrode material was used as the positive electrode and a metallic lithium sheet was used as the negative electrode to prepare a button battery, and a performance evaluation test of the material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0-4.3V, and current density 0.1C, and the discharge specific capacity was 203 mAh / g and the coulombic efficiency was 88.2%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 88.5%, and the capacity retention rate was 92.5% after 60 weeks of 1C cycle. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0-4.3V, and current density 0.5C, showing that the DCR at 10% SOC of the material was 42.8Ω, and the DCR growth after 50 cycles was 41%. These results confirmed that the amount of cobalt source during coating affects the coating effect, and the electrochemical performance of the dot-coated high-nickel positive electrode material is still different from the wrinkle-coated high-nickel ternary positive electrode material in Example 2. Comparative Example 4

[0064] Cobalt-aluminum co-coated Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 O2·Li 0.62 CoAl 0.2 The O2 high nickel positive electrode material is produced, and the production method is specifically as follows: (1) Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 O2 Production of lithium-containing metal oxides Lithium hydroxide monohydrate and 100g of Ni 0.90 Co 0.05 Mn 0.05 The mixed raw materials were heated from room temperature to 500°C at a rate of 3°C / min in an oxygen atmosphere and calcined for 3 hours, then heated to 850 and calcined for 12 hours, naturally cooled to room temperature, and then Li 1.05 Ni0.90 Co 0.05 Mn 0.05 O2 lithium-containing metal oxide was obtained. (2) Cobalt-aluminum co-coated Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 O2·Li 0.62 CoAl 0.2 O2 High Nickel Positive Electrode Material Production 100g of Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 Add 18,500 ppm of cobalt acetate and 1,500 ppm of aluminum hydroxide to the lithium-containing metal oxide, mix uniformly, and then heat at a rate of 3°C / min in an oxygen atmosphere at 715°C. The calcination time is 7 hours. After cooling to room temperature, the cobalt-aluminum co-coated Li 1.05 Ni 0.90 Co 0.05 Mn 0.05 Al 0.05 O2 high nickel positive electrode material was obtained.

[0065] Comparative Example 4 had the same composition as that of the nickel-cobalt-manganese in Example 3, except that cobalt acetate was used as the cobalt source instead of cobalt hydroxide or cobalt oxyhydroxide having a small particle size, and was simultaneously subjected to coating treatment with cobalt and aluminum.

[0066] The material produced in Comparative Example 4 was subjected to an FE-SEM test, and the results are shown in FIG. 11. The high-nickel positive electrode material produced in Comparative Example 4 was able to form a thin coating layer on the surface, but was unable to form a wrinkled morphology, and many aggregated particles were present on the surface. The particle diameter range of the high-nickel positive electrode material particles produced in Comparative Example 4 was 1.1 to 4.7 μm, the median diameter was 5.53 μm, and the specific surface area was 0.76 m. 2 The material had a specific gravity of 3.47 g / cc and a powder conductivity of 0.020 S / cm. The cobalt-aluminum coated high nickel ternary cathode material produced in Comparative Example 4 was subjected to XRD testing to determine its I (003) / I (104)The ratio was 2.19.

[0067] A button battery was prepared using the high nickel ternary positive electrode material produced in Comparative Example 4 as the positive electrode and a metallic lithium sheet as the negative electrode, and a performance evaluation test of the material was performed. Charge and discharge were performed under conditions of 25°C, voltage range 3.0 to 4.3V, and current density 0.1C, and the discharge specific capacity was 203mAh / g and the coulombic efficiency was 88.4%. After that, 0.2C / 0.5C / 1.0C / 2.0C rate discharge was performed, and the discharge retention rate at 2.0C / 0.2C was 88.7%, and when the 1C cycle was continued for 60 weeks, the capacity retention rate was 92.6%. At the same time, a DCR test was performed under conditions of 45°C, voltage range 3.0 to 4.3V, and current density 0.5C, and the result showed that the DCR at 10% SOC of the material was 36.7Ω, and the DCR growth after 50 cycles was 49%. These results confirmed that the choice of cobalt source during coating affects the coating effect, and that the electrical performance of the high-nickel positive electrode material differs depending on the coating form, with the wrinkled-coated high-nickel positive electrode material showing the best performance in terms of capacity, cycle performance, rate performance and DCR performance.

Claims

1. A ternary positive electrode material for a lithium ion battery having a coated structure, characterized in that a core of the coated structure contains a lithium composite metal oxide, the lithium composite metal oxide contains nickel, cobalt, and manganese, an outer coating layer of the coated structure is wrinkled, the wrinkled outer coating layer coats a surface of the lithium composite metal oxide, and the wrinkled outer coating layer is mainly a cobalt-containing lithium metal oxide.

2. The ternary positive electrode material is Li a Ni x Co y Mn 1-x-y O 2 Li m CoM n O 2 and 1.0≦a≦1.15, 0.8≦x<1, 0<y≦0.2, 0<1-x-y, and 0.5≦m<1, 0≦n≦0.2, wherein M is one or more elements selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y. The ternary positive electrode material for lithium ion batteries according to claim 1,

3. The ternary cathode material for lithium ion batteries according to claim 1, characterized in that the particle size range of said ternary cathode material is 1.0-10.0 μm, preferably 1.0-5.0 μm.

4. The specific surface area of ​​the ternary positive electrode material is 0.3 to 0.9 m 2 / g, preferably 0.7 to 0.9 m 2 2. The ternary positive electrode material for a lithium ion battery according to claim 1, characterized in that the ternary positive electrode material for a lithium ion battery has a molecular weight of 1.001 to 1.001 g / g.

5. 2. The ternary positive electrode material for lithium ion batteries according to claim 1, characterized in that the outer coating layer further contains one or more M elements selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg and Y.

6. The ternary positive electrode material for lithium ion batteries according to any one of claims 1 to 5, characterized in that the cobalt content of the outer coating layer is 6000 to 32000 ppm, and the coating thickness of the outer coating layer is 0.1 to 0.6 μm.

7. The ternary positive electrode material for lithium ion batteries according to claim 6, characterized in that the cobalt content of the outer coating layer is 6000-19000 ppm, and the coating thickness of the outer coating layer is 0.1-0.4 μm.

8. The ternary positive electrode material for a lithium ion battery according to any one of claims 1 to 5, characterized in that the cobalt-containing lithium metal oxide in the outer coating layer is obtained by reacting a cobalt source with a lithium compound remaining on a surface layer of the lithium composite metal oxide.

9. I in the XRD pattern of the ternary positive electrode material (003) / I (104) The ternary positive electrode material for lithium ion batteries according to any one of claims 1 to 5, characterized in that the ratio of is 1.5 to 3.

0.

10. The ternary positive electrode material for lithium ion batteries according to any one of claims 1 to 5, characterized in that the range of wrinkle degree X of the ternary positive electrode material under a scanning electron microscope is 0.1 to 0.8, X = h / t, h is the height of a single wrinkled morphology on a crystal grain surface of the single ternary positive electrode material, 20 nm ≦ h ≦ 120 nm, t is the width of a single wrinkled morphology on a crystal grain surface of the single ternary positive electrode material, 100 nm ≦ t ≦ 200 nm.

11. 1. A method for producing a ternary cathode material for a lithium ion battery, comprising: 1) mixing a lithium source and a ternary precursor material in a molar ratio of 1 to 1.15:1, and then performing multi-stage high-temperature sintering in an oxygen atmosphere after mixing, and obtaining a lithium composite metal oxide after cooling to room temperature; and step 2) of mixing the lithium composite metal oxide obtained in step 1) with a cobalt source or a compound of a cobalt source and an M element, and then sintering the mixture in an oxygen atmosphere to obtain a ternary positive electrode material, The method for producing a ternary positive electrode material for a lithium ion battery, wherein the cobalt source is selected from cobalt hydroxide or cobalt oxyhydroxide, and the amount of the cobalt source added is 10000 ppm to 50000 ppm.

12. 12. The method according to claim 11, wherein the lithium source is one or more selected from the group consisting of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate, and the compound of the M element is a compound of at least one element selected from the group consisting of Zr, Si, La, Ba, Sr, Nb, Al, Mg, and Y.

13. 12. The method according to claim 11, wherein the high-temperature sintering in step 1) is a two-stage calcination, the temperature range of the first stage calcination is 400-600°C, the sintering time is 2-4 hours, and the temperature range of the second stage calcination is 600-1000°C, the sintering time is 8-15 hours.

14. The method according to claim 13, characterized in that in step 2), the sintering temperature is 600-900°C, and the sintering time is 5-12 hours, preferably 650-850°C, and the sintering time is 6-9 hours.

15. The method according to any one of claims 11 to 14, characterized in that the amount of the cobalt source added is 10000 to 30000 ppm, and the median diameter D50 of the cobalt source is 0.8 to 4.0 μm, preferably 1.0 to 2.0 μm.

Citation Information

Patent Citations

  • Nickel-cobalt-lithium manganate ternary cathode material and preparation method thereof

    CN110474026A